A history of reading - Manguel, Alberto. (Viking, 1996)
At one magical instant in your early childhood, the page of a book - that string of confused, alien ciphers - shivered into meaning. Words spoke to you, gave up their secrets; at that moment, whole universes opened. You became, irrevocably, a reader. Noted essayist Alberto Manguel moves from this essential moment to explore the 6000-year-old conversation between words and that magician without whom the book would be a lifeless object: the reader. Manguel lingers over reading as seduction, as rebellion, as obsession, and goes on to trace the never-before-told story of the reader's progress from clay tablet to scroll, codex to CD-ROM.